Manajemen Diagnostik Kesulitan Belajar Berbasis Nilai Islam dalam Pembelajaran Remedial di Lembaga Pendidikan Islam - Sartika; Afnibar; Ulfatmi (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
This article explores the management of diagnostic assessment for learning difficulties integrated with Islamic values in the implementation of remedial learning within Islamic educational institutions. Using a library research approach, this study analyzes theoretical concepts, principles, and relevant scholarly findings from books and reputable journals. The results reveal that diagnostic management is essential for systematically identifying students’ learning barriers and determining appropriate remedial interventions. Integrating Islamic values into remedial learning not only supports cognitive improvement but also strengthens spiritual, moral, and emotional dimensions in accordance with the principle of rahmatan lil ‘alamin. Core values such as patience, trustworthiness, cooperation (ta‘awun), and excellence (ihsan) provide an ethical foundation for educators in conducting humanistic, fair, and transformative diagnostic and remedial processes. Artikel ini mengkaji manajemen diagnostik kesulitan belajar yang dipadukan dengan nilai-nilai Islam dalam pelaksanaan pembelajaran remedial di lembaga pendidikan Islam. Melalui pendekatan penelitian kepustakaan, studi ini menganalisis konsep teoretis, prinsip, serta temuan ilmiah yang relevan dari buku dan jurnal bereputasi. Hasil kajian menunjukkan bahwa manajemen diagnostik berperan penting dalam mengidentifikasi hambatan belajar peserta didik secara sistematis dan menentukan intervensi remedial yang tepat. Integrasi nilai Islam dalam pembelajaran remedial tidak hanya mendorong perbaikan kognitif, tetapi juga penguatan spiritual, moral, dan emosional sesuai prinsip rahmatan lil ‘alamin. Nilai-nilai seperti sabar, amanah, ta‘awun, dan ihsan menjadi landasan etis bagi pendidik dalam menjalankan proses diagnosis dan remedial yang humanis, adil, dan transformatif.